ChemInform Abstract: Studies on Synthesis of Spirolactone Annulated Bicyclo[2.2.2]octanes: Tricyclic Core of Yaoshanenolides. Issue 51 (23rd December 2014) - Das, Beauty; Mobin, Shaikh M.; Singh, Vishwakarma
Abstract This describes the syntheses of compounds, e.